One new species and one newly recorded species in the subgenus Myothorax Murray, 1864 from China (Coleoptera: Nitidulidae: Carpophilinae: Carpophilus) - Chen, Xiaoxiao; Hui, Ziyan; Huang, Min (Zootaxa, 2020)
One new species, Carpophilus (Myothorax) brunneus sp. nov., and one newly recorded species, Carpophilus (Myothorax) nepos Murray, 1864, are described or redescribed from China, photographed, and illustrated in detail.